2018
DOI: 10.13052/jmm1550-4646.1443
|View full text |Cite
|
Sign up to set email alerts
|

Tutorial on UAVs: A Blue Sky View onWireless Communication

Abstract: The growing use of Unmanned Aerial Vehicles (UAVs) for various applications requires ubiquitous and reliable connectivity for safe control and data exchange between these devices and ground terminals. Depending on the application, UAV-mounted wireless equipment can either be an aerial user equipment (AUE) that co-exists with the terrestrial users, or it can be a part of wireless infrastructure providing a range of services to the ground users. For instance, AUE can be used for real-time search and rescue and/o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 92 publications
1
54
0
Order By: Relevance
“…For instance, in telecommunications, collision avoidance is often used for describing techniques used to avoid resource contention during an information transmission. Moreover, the same term is used for describing a physical collision, as in [3,5], but this definition is still much more general than the one used in avionics.…”
Section: B Need Of Interdisciplinary Terminologymentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, in telecommunications, collision avoidance is often used for describing techniques used to avoid resource contention during an information transmission. Moreover, the same term is used for describing a physical collision, as in [3,5], but this definition is still much more general than the one used in avionics.…”
Section: B Need Of Interdisciplinary Terminologymentioning
confidence: 99%
“…For this reason, several technologies were used in [13] such as LoRa (Long Range Wide Area Network), and APRS (Automatic Packet Reporting System). In [3], it was shown that Wi-Fi also suffers from interference, which results in problems with establishing a reliable connection between 2 nodes (2 UAVs, or UAV and the ground controller/UTM infrastructure). However, embedding the coordinates and drone ID in Wi-Fi Service Set Identifier (SSID) allows to broadcast this critical data in an ADS-B like manner, as it was shown in [14].…”
Section: B Case Study 1: Ads-b Like Messaging Via Wi-fimentioning
confidence: 99%
See 2 more Smart Citations
“…Recommendations for future work includes an investigation of the impact of emergency traffic on the various communication interfaces at different altitudes [28,33]. A set of aerial platforms are considered in [34] for emergency communication using delay-tolerant networks (DTN) on sub-GHz frequencies.…”
Section: Performance Indicatorsmentioning
confidence: 99%